The effect of parity, history of preeclampsia, and pregnancy care on the incidence of subsequent preeclampsia in multiparous women with SLE. Issue 4 (4th July 2021) - Maeda, Yuto; Kaneko, Kayoko; Ogawa, Kohei; Sago, Haruhiko; Murashima, Atsuko
Abstract: Objectives: To clarify the correlation between preeclampsia and parity and to identify protective factors against preeclampsia in multiparous women with systemic lupus erythematosus (SLE). Methods: We conducted a single-center, retrospective chart review study of 85 pregnant women. We used multiple logistic regression analysis to assess the association between parity and preeclampsia in women with SLE, and described the detailed clinical courses and management of four women with a history of severe preeclampsia and of a woman who experienced preeclampsia during her latest pregnancy. Results: Multiparity was significantly associated with a low risk of preeclampsia (adjusted odds ratio: 0.08; 95% confidence interval: 0.01–0.95). One multiparous woman without a history of preeclampsia developed preeclampsia during her latest pregnancy; she had critical risk factors for preeclampsia, including chronic kidney disease and hypertension, and was not administered aspirin. In contrast, four multiparous women with a history of severe preeclampsia received adequate medications; they did not develop recurrent preeclampsia and delivered live newborns. Conclusions: Multiparity and maintenance therapy for SLE before and during pregnancy and preventive treatment for preeclampsia may improve outcomes in subsequent pregnancies.